1993
DOI: 10.1192/bjp.163.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Acting on Delusions. I: Prevalence

Abstract: Associations between delusions and abnormal behaviour were retrospectively assessed in a sample of 83 consecutively admitted deluded subjects. All were interviewed about events in the previous month using a new measure of delusional phenomenology and action. For 59 subjects this information was supplemented by informant interviews. Clinical consensus was reached concerning the probability that actions reported by informants were linked to delusions. Half of the sample reported that they had acted at least once… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
175
1
4

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(184 citation statements)
references
References 1 publication
2
175
1
4
Order By: Relevance
“…Stompe et al (1999) reported that persecution was the most common delusional belief type among 126 Austrian and 108 Pakistani people diagnosed with schizophrenia. Persecutory delusions are associated with strong negative affect, and are the delusion type most likely to be acted upon (Appelbaum, Robbins, & Roth, 1999;Wessely et al, 1993). The presence of persecutory delusions has been found to predict hospital admission on first contact with psychiatric services (Castle, Phelan, Wessely, & Murray, 1994).…”
Section: The Clinical Significance Of Persecutory Delusionsmentioning
confidence: 99%
“…Stompe et al (1999) reported that persecution was the most common delusional belief type among 126 Austrian and 108 Pakistani people diagnosed with schizophrenia. Persecutory delusions are associated with strong negative affect, and are the delusion type most likely to be acted upon (Appelbaum, Robbins, & Roth, 1999;Wessely et al, 1993). The presence of persecutory delusions has been found to predict hospital admission on first contact with psychiatric services (Castle, Phelan, Wessely, & Murray, 1994).…”
Section: The Clinical Significance Of Persecutory Delusionsmentioning
confidence: 99%
“…Delírios de grandeza e religioso relacionaram-se com aumento na convicção, enquanto delírios persecutórios foram fortemente marcados por afetos negativos e por propensão para agir (Appelbaum et al, 1999;Wessely et al, 1993). Comportamento desviante parece associar-se tanto ao grau de convicção do delírio como com a resposta afetiva a este (Dalgalarrondo et al, 2003).…”
Section: Violência Entre Pacientes Com Transtornos Mentaisunclassified
“…Importantly, most do. Wessely et al [99] found that 60% of their sample of deluded individuals 6 reported at least one action based on delusion; third-party informants reported that 52% of the sample probably or definitely acted on delusions. Persecutory delusions were significantly more likely to be acted upon than other beliefs.…”
Section: Delusions As Adaptations For Exploitative Deceptionmentioning
confidence: 99%
“…These are the most common type of delusions [9]. Individuals with these delusions can give very convincing accounts of the reputed threat, behave consistently with the delusion [99], and give cues of genuine fear and distress [100].…”
Section: Hypothesized Functionmentioning
confidence: 99%